The torque-velocity relation of elite soccer players - Borges, G. M.; Vaz, M. A.; De La Rocha Freitas, C. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim. The purpose of this study was to describe the torque-velocity (T-V) relationship during concentric and eccentric contractions of the lower limb muscles in professional soccer players. Methods. Soccer players (n=10) that were training systematically for at least 5 years were compared with moderately active individuals (n=13), that were not engaged in any systematic physical activity program in the last 5 years. Peak torque, and angle-specific torque at knee angles of 0.52 rad and 1.04 rad were evaluated during maximal concentric and eccentric contractions at 0.52 rad·sec-1, 1.04 rad·sec-1, 1.57 rad·sec-1, 2.09 rad·sec-1, 3.14 rad·sec-1, 4.19 rad·sec-1 and 5.23 rad·sec-1 angular velocities. Results. During concentric contractions, inverse hyperbolic relationships were fitted for the two groups [T = Tmax + (a · b)/(b + V)], with values for a and b of 1.4 and 347.6 for the control group, respectively, and 1.9 and 605.4 for the soccer players, respectively. When torque was measured at 0.52 rad, the torque-velocity relationship presented a plateau at low velocities in the two groups investigated. When torque was measured at 1.04 rad, the torque-velocity relationship presented a plateau at low velocities in the control group, in which force did not increase significantly as velocity was decreased. The plateau was not observed in soccer players. Peak torque and torque measured at 1.04 rad were higher in the soccer players than in the control group in all velocities investigated. However, the biggest difference was found in lower velocities of contraction. Conclusion. Soccer players produced a higher muscle torque in the lower limb than moderately active individuals, and this difference was bigger when the velocities were low.